Hubungan peran guru Pendidikan Agama Islam dengan karakter beragama siswa di SMA - Salam, Dimas Ibrahim; Muhyani (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This study aims to analyse the relationship between the role of Islamic Religious Education (PAI) teachers and students religious character at Dwiwarna High School in Bogor Regency. The role of Islamic Education Teacher is not only as a teacher, but also includes functions as a guide, role model, and motivator in the formation of students religious character. A quantitative approach was used in this study with a correlational method. The research sample was 45 students from classes X and XI who were selected throught purposive sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability. The results showed a significant positive relationship between the role of PAI teachers and students religious character (r = 0,561, p < 0,05). This finding reinforces the importance of optimising the role of PAI teachers in fostering students spiritual character. Abstrak Penelitian ini bertujuan untuk menganalisis hubungan antara peran guru Pendidikan Agama Islam (PAI) dengan karakter beragama siswa di SMA Dwiwarna Kabupaten Bogor. Peran Guru PAI tidak hanya sebagai pengajar, tetapi juga mencakup fungsi sebagai pembimbing, teladan, dan motivator dalam pembentukan karakter religius siswa. Pendekatan kuantitatif digunakan dalam penelitian ini dengan metode korelasional. Sampel penelitian sebanyak 45 siswa dari kelas X dan XI yang dipilih melalui teknik purposive sampling. Instrumen yang digunakan adalah kuesioner yang telah diuji validitas dan reliabilitasnya. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara peran guru PAI dengan karakter beragama siswa (r = 0,561, p < 0,05). Temuan ini memperkuat pentingnya optimalisasi peran guru PAI dalam membina karakter spiritual peserta didik.